Clarifying the Behavioral Economics of Social Anxiety Disorder: Effects of Interpersonal Problems and Symptom Severity on Generosity. (January 2016) - Rodebaugh, Thomas L.; Heimberg, Richard G.; Taylor, Kristin P.; Lenze, Eric J.
Social anxiety disorder is associated with lower interpersonal warmth, possibly explaining its associated interpersonal impairment. Across two samples, we attempted to replicate previous findings that the disorder's constraint of interpersonal warmth can be detected via behavioral economic tasks. We also tested the test–retest stability of task indices. Results indicated that factors associated with social anxiety disorder (and not the disorder itself), such as the severity of social anxiety and more extreme interpersonal problems, lead to less generous behavior on the economic task examined. Results were clearest regarding fine-grained indices derived from latent trajectories. Unexpectedly, the combination of generalized anxiety disorder and higher depression also restricted generosity. Two of three indices showed acceptable test–retest stability. Maladaptive giving behavior may be a treatment target to improve interpersonal functioning in psychiatric disorders; therefore, future work should more precisely characterize behavioral economic tasks, including basic psychometric work (i.e., tests of reliability and validity).